Fathers' perspectives on and involvement in the education of their children with developmental disabilities - Alonzo, Miguelita B. (2005)
A researcher-designed questionnaire was utilized to measure fathers' perspectives on three factors: personal-related, child-related and school-related and also the extent of their involvement. Findings revealed that they believe that special education is built upon Pro-life, Pro-humanity and Pro-God orientation and principles. Their perspectives implied acceptance of their special children as they recognize the responsibility of involving themselves in caring for special children and understanding their uniqueness. On the whole, there is likewise a significant relationship between fathers' involvement and overall perspectives covering all the three factors.
"May 2005."
Thesis (M.A. Special Education)--University of the Philippines Diliman.
Keywords: Fathers of children with disabilities -- Philippines -- Metropolitan Manila; Special education -- Parent participation -- Philippines -- Metropolitan Manila; Developmentally disabled children -- Education -- Philippines -- Metropolitan Manila